Ultrathin, flexible and transparent graphene-based triboelectric nanogenerators for attachable curvature monitoring. (4th June 2019) - Liu, Zhaoxian; Zhao, Zhizhen; Zeng, Xiangwen; Fu, Xiuli; Hu, Youfan
Abstract: Pursuits of wearable electronics include the features of flexible, self-powered, and even being ultrathin and transparent for a better fit on different curved surfaces in an imperceptible way. In this paper, by stacking two graphene-covered parylene films layer by layer and introducing serpentine structures in one parylene film as the spacer, ultraflexible triboelectric nanogenerators (TENGs) with a total thickness of 5.5 μ m and a transmittance of 80% were achieved. Under the stimulation of vertical impacts at frequencies of 0.5 Hz, 1 Hz, 1.5 Hz, 2 Hz, and 2.5 Hz, an open-circuit (OC) voltage of 3 V was maintained in a TENG measuring 2 × 2 cm 2 throughout all the cases, which indicated a good mechanical stability of the device. When the TENG was bent, there was an increase in OC voltage and short-circuit current in response to an increased curvature. Due to its ultrathin nature and being sensitive to curvature, the TENG was demonstrated to serve as a self-powered curvature sensor for movement monitoring when conformably attached on the finger joint.